Gait speed as a mediator of the effect of sarcopenia on dependency in activities of daily living. Issue 5 (8th May 2019) - Perez‐Sousa, Miguel A.; Venegas‐Sanabria, Luis Carlos; Chavarro‐Carvajal, Diego Andrés; Cano‐Gutierrez, Carlos Alberto; Izquierdo, Mikel; Correa‐Bautista, Jorge Enrique; Ramírez‐Vélez, Robinson
Abstract: Background: Sarcopenia in older adults is strongly associated with an increase in dependency in activities of daily living (ADL) and with a decline in gait speed. Interestingly, gait speed has been shown to independently predict mortality. In this context, our study aimed to explore the mediator role of gait speed on the relationship between sarcopenia and dependency in ADL. Methods: A cross‐sectional study was conducted in Colombia, 19 705 older adults with a mean age of 70 years, 55.6% women, 16.1% with sarcopenia, and 14.7% mild, moderate, or severe dependency in ADL, according to 'SABE Survey 2015'. Sarcopenia was assessed by calf circumference and ADL dependence through the Barthel Index. Gait speed was measured over a distance of 3 m. The association between sarcopenia condition and gait speed and dependency level was analysed by linear regression adjusted by covariates. To examine whether gait speed mediated the association between sarcopenia and dependence components of physical function, simple mediation models were generated using ordinary least squares with the macro PROCESS version 3.2, adjusted for age, sex, and body mass index (BMI). Results: Significant differences ( P < 0.05) were found in gait speed and dependency in ADL between the sarcopenia and non‐sarcopenia groups after adjusting for age, sex, and BMI. BMI was significantly higher in the non‐sarcopenia group whereas dependency was significantly higher in the sarcopenia group (19.6% vs. 13.8%). Results from mediation model regression analysis indicated a significant and direct detrimental effect of sarcopenia on dependency in ADL ( β = −0.05; P < 0.001), and a significant indirect effect of gait speed on the direct effect (−0.009 to −0.004). Conclusions: The negative effect of sarcopenia on functional dependence was mediated by the gait speed. Therefore, gait speed may positively influence the detrimental effect of sarcopenia for dependency, after adjusting for age, gender, and BMI. Consequently, physical exercise should be promoted and focused to circumvent the gait speed decline associated with age in older people with sarcopenia.